When is an obscurin variant pathogenic? The impact of Arg4344Gln and Arg4444Trp variants on protein–protein interactions and protein stability. Issue 12 (12th January 2021) - Fukuzawa, Atsushi; Koch, Daniel; Grover, Sarah; Rees, Martin; Gautel, Mathias
Abstract: Obscurin is a giant muscle protein that connects the sarcomere with the sarcoplasmic reticulum, and has poorly understood structural and signalling functions. Increasingly, obscurin variants are implicated in the pathophysiology of cardiovascular diseases. The Arg4344Gln variant (R4344Q) in obscurin domain Ig58, initially discovered in a patient with hypertrophic cardiomyopathy, has been reported to reduce binding to titin domains Z8-Z9, impairing obscurin's Z-disc localization. An R4344Q knock-in mouse developed a cardiomyopathy-like phenotype with abnormal Ca 2+ -handling and arrhythmias, which were attributed to an enhanced affinity of a putative interaction between obscurin Ig58 and phospholamban (PLN) due to the R4344Q variant. However, the R4344Q variant is found in 15% of African Americans, arguing against its pathogenicity. To resolve this apparent paradox, we quantified the influence of the R4344Q variant (alongside another potentially pathogenic variant: Arg4444Trp (R4444W)) on binding to titin Z8-Z9, novex-3 and PLN using pull-down assays and microscale thermophoresis and characterized the influence on domain stability using differential scanning fluorimetry. We found no changes in titin binding and thermostability for both variants and modestly increased affinities of PLN for R4344Q and R4444W. While we could not confirm the novex-3/obscurin interaction, the PLN/obscurin interaction relies on the transmembrane region of PLN and is not reproducible in mammalian cells, suggesting it is an in vitro artefact. Without clear clinical evidence for disease involvement, we advise against classifying these obscurin variants as pathogenic.